Pembentukan Struktur Negosiasi Kota Surakarta: Kritik Nalar ‘Best Practices’ dalam Penyelenggaraan Pemerintahan - Hendra Try Ardianto (Jurnal Ilmu Sosial dan Ilmu Politik, 2011)
This paper attempts to describe two fundamental ideas about best practices. Firstly, criticism of the notion of "best practices" that is very agent-centric. It asserts that the discourse "best practices" should not be separated from socio political structures. In the case of Surakarta, the agency perspective that put Jokowi as the center of innovation was apparently failed to understand the overall dynamics of governance practices and tend to be misleading. Secondly, this paper tries to restore the meaning of participation as a form of politicization, not merely procedural- managerial affairs. Thus, participation is not only a mobilization to encourage the dreams of innovation, rather, participation is a matter of negotiation in which the contestation of interests between people, nations, and the market becomes the main case.